The Impact of Toxic Leadership on Job Combustion (An Exploratory Study of the Views of the Fabric of Babylon Factory Staff) - Ali, Ibtihal Faris (International Journal of Psychosocial Rehabilitation, 2020)
For many organizations in general, toxic focus has become the focus of past years for toxic leadership of leaders’ behavior, leading to negative outcomes that can lead to toxic leadership to reduce staff efficiency and negatively affect the relationship between the cost of beneficiary organizations and at the same time, causing In high absenteeism, which increases staff mobility, poor performance, and individual thinking despite the growing interest in the science department, he noted that systematic and scientific field work on toxic leadership is inadequate, and it is clear to us the importance of research by searching for the problem through one of the questions which focused on whether there is a correlation and effect between the search variables and in this light was built a hypothetical model emerged from the hypotheses of the main and sub search. To test the validity of the hypotheses collected through a questionnaire tool prepared for this purpose and tested for itself the size of (65) workers in (Babylon Textile Factory), the data were analyzed using a set of statistics were extracted methods and results using software and in the light of the results of the study showed that there are A strong correlation between the authoritarian administrative variable of toxic leadership and functional combustion (77%).Finally, the research made a set of recommendations, including attention to the issue of job combustion among workers at the Babylon Textile Factory, because of its negative impact on the productivity of workers, and to take measures to reduce levels among workers.